The overtraining syndrome - Susta, S. (Triathlon Medicine, 2019)
The overtraining syndrome (OTS) is a complex, systemic clinical condition affecting athletes exposed to a combination of high training loads and insufficient recovery. OTS could be described as a failure of the athlete's body to cope with increasing conditioning loads, usually administered to stimulate adaptations leading to enhanced performance. During conditioning programmes, performance may be reduced, temporarily, this condition being a physiological response to training known as 'functional overreaching'. In this case, performance is reduced for up to few weeks and fully restored after an adequate recovery. When the athlete's body fails to adequately react to training loads and performance is not restored/improved after a longer period of recovery, 'non-functional overreaching' (NFOR), and OTS should be considered as potential diagnostic options. The chapter aims to provide guidance on how to manage triathletes presenting with common signs and symptoms of OTS, and on how to use specific tools to make a diagnosis of OTS. The last part of this chapter is focused on 'monitoring' triathletes: in particular, emphasis is placed on the most effective preventive approaches reflecting the clinical complexity of NFOR/OTS and aiming at preserving triathletes' health status.